2018
DOI: 10.3126/hn.v23i0.20829
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Climate Change and its Effects in the Western Mountainous Water Basin of Nepal

Abstract: This study was conducted in the period of January 2014 to December 2015. The main objective of the study was to investigate the impact of climate change in the water basin and its catchment areas. The method was a survey of relevant literatures. Climate change is a big issue not only in developed countries but also in developing countries. The study found that the temperature is rising with 2.00 C on average per annum in western Nepal. This is relatively 3 times higher than lower temperature increase within th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…Thus, the vulnerability index is a popular measure to assess disasterinduced vulnerability at the household and community level. Theoretically, vulnerability assessment methods are multiple (Turner et al, 2003;Hoddinott & Quisumbing, 2003;Petty and Seaman, 2004;Cannon et al, 2005;Gallopin, 2006;Banerjee et al, 2007;Holzmann et al, 2008;Lawrence et al, 2008;O'Brien et al, 2009;Naude et al, 2009;Casale et al, 2010;Kalibala et al, 2012;UNICEF, 2012, Kureya, 2013Bista et al, 2018;Bista, 2019c;Bista, 2020). They are a) Local Vulnerability Assessment Method (LVAM), b) Livelihood Vulnerability Assessment Method, c) Household Vulnerability Assessment Method (HVAM), d) Household Livelihood Security Analysis Method (HLSAM), and e) Climate Vulnerability Assessment Method (CVAM).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the vulnerability index is a popular measure to assess disasterinduced vulnerability at the household and community level. Theoretically, vulnerability assessment methods are multiple (Turner et al, 2003;Hoddinott & Quisumbing, 2003;Petty and Seaman, 2004;Cannon et al, 2005;Gallopin, 2006;Banerjee et al, 2007;Holzmann et al, 2008;Lawrence et al, 2008;O'Brien et al, 2009;Naude et al, 2009;Casale et al, 2010;Kalibala et al, 2012;UNICEF, 2012, Kureya, 2013Bista et al, 2018;Bista, 2019c;Bista, 2020). They are a) Local Vulnerability Assessment Method (LVAM), b) Livelihood Vulnerability Assessment Method, c) Household Vulnerability Assessment Method (HVAM), d) Household Livelihood Security Analysis Method (HLSAM), and e) Climate Vulnerability Assessment Method (CVAM).…”
Section: Introductionmentioning
confidence: 99%
“…Rice yield is sensitive to climate change, particularly temperature (Schlenker & Roberts, 2009) and extended drought periods (Yoshida et al, 2015). Temperature is increasing at an average of 0.06° C per year (Bista et al, 2018), impacting soil moisture because of increased evapotranspiration. Rainy days are lessening at a rate of 0.8 days per year, leading to a delay in monsoon season and shortage of water, modifying cropping patterns and crop maturity duration (Regmi & Adhikari, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Climate change had been observe more severely in Hindu Kush Himalayan region including Nepal [41][42][43]. Different sectors such as socio-economic, biodiversity, livelihood, water resources and energy are already experiencing negative impact of climate change in the country [44][45][46]. This paper provides a systematic quantitative analysis of the academic literature on the impacts of climate change and vulnerability assessment in study area.…”
Section: Introductionmentioning
confidence: 99%
“…The elevation of the area ranges from 420 meters to 1480 meters above the sea level. The special climate change fund project (EbA SSC) determined this study areas as suitable because Lamjung and Mugu districts were found to be more vulnerable in terms of climate change among other districts in Nepal[44].…”
mentioning
confidence: 99%